DNA modifications that do not cause gene mutations confer the potential for mutagenicity by combined treatment with food chemicals. (July 2019) - Ishii, Yuji; Yokoo, Yuh; Kijima, Aki; Takasu, Shinji; Ogawa, Kumiko; Umemura, Takashi
Abstract: Cell proliferation plays a key role in fixing mutations induced by DNA damage. We clarified whether this phenomenon occurred after combined treatment with chemicals in food. The effects of antibiotic flumequine (FL), a residue of veterinary medicinal products in foodstuffs, on mutagenicity in the liver were examined in mice treated with estragole (ES), a natural food flavouring compound. Gpt delta mice were orally administered 10 or 100 mg/kg/day ES and simultaneously fed a diet containing 0.4% FL for 4 weeks. Proliferating cell nuclear antigen-positive cells and cell cycle-related genes were additively increased in the livers of combined treatment groups as compared with high-dose ES or FL groups. Mutant frequencies (MFs) in gpt after cotreatment with low-dose ES and FL were significantly increased, although treatment with ES alone increased MFs only in the high-dose group. Sult1a1 mRNA levels were unchanged after FL treatment. Liquid chromatography with tandem-mass spectrometry analysis showed that FL did not affect the amount of ES-specific DNA adducts in the livers, indicating that FL treatment did not influence metabolic pathways of ES. Thus, enhancement of the mutagenic potential of a chemical by chemical-induced cell proliferation may occur as a result of the combined effects of chemicals in food. Graphical abstract: Image 1 Highlights: The combined effects of chemicals in food were examined using estragole, a natural flavour, and antibiotics flumequine. Compensatory cell proliferation induced by flumequine exerted enhancing effects on estragole mutagenicity. The present data implies that microenvironmental modifier in food could raise risk hazard of genotoxic chemicals.